Reflecting 1960s–1970s New York Society in Patti Smith's Just Kids: A Sociology of Literature Perspective - Mailida Nur Setiana; Muizzu Nurhadi; Nailil Muna (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines how Patti Smith’s memoir Just Kids (2010) reflects the social conditions of New York City during the 1960s and 1970s, a period characterized by the tension between conventional social values and the emergence of bohemian culture. Previous studies have primarily focused on the memoir’s autobiographical aspects, artistic collaboration, identity, and trauma, while comparatively little attention has been given to its portrayal of the broader social realities of the era. This study addresses that gap by analyzing the memoir through Alan Swingewood’s sociology of literature, which views literary works as reflections of the social, historical, and cultural contexts in which they are produced. Employing a descriptive qualitative method, the study collected textual data through close reading, classified the data into thematic categories, and interpreted them in relation to the historical context of 1960s–1970s New York. The findings reveal that Just Kids portrays a society shaped by traditional expectations surrounding sexuality, marriage, religion, and family, while also depicting economic hardship, housing insecurity, and low-wage employment experienced by emerging artists. The memoir further reflects the impact of major historical events, including the Vietnam War, the assassination of Robert F. Kennedy, and the attempted assassination of Andy Warhol, demonstrating how these events influenced both collective consciousness and individual lives. Overall, the findings confirm that Just Kids functions not only as a personal memoir but also as a social document that captures the complexities of New York society during a period of cultural transformation and the emergence of bohemian culture as an alternative way of life.